2012
DOI: 10.1155/2012/801306
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of the First Experience with Bevacizumab for the Treatment of Patients with Recurrent High-Grade Glioma in Two Belgian University Hospitals

Abstract: Background. Bevacizumab (BEV), a humanized immunoglobulin G1 monoclonal antibody that inhibits VEGF has demonstrated activity against recurrent high-grade gliomas (HGG) in phase II clinical trials. Patients and Methods. Data were collected from patients with recurrent HGG who initiated treatment with BEV outside a clinical trial protocol at two Belgian university hospitals. Results. 19 patients (11 M/8 F) were administered a total of 138 cycles of BEV (median 4, range 1–31). Tumor response assessment by MRI wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In adult HGG, the use of bevacizumab (BVZ), an anti-angiogenic agent that blocks vascular endothelial growth factor (VEGF), has shown promising results and a survival benefit in patients with recurrent HGG ( Narayana et al, 2009 ; Huylebrouck et al, 2012 ; Morris, 2012 ). These findings led to the development of a pediatric trial within the PBTC-022 utilizing BVZ and CPT-11 in children with recurrent CNS tumors, including a HGG and diffuse intrinsic pontine glioma (DIPG) strata ( Gururangan et al, 2010 ).…”
Section: Treatment Strategies and Outcomesmentioning
confidence: 99%
“…In adult HGG, the use of bevacizumab (BVZ), an anti-angiogenic agent that blocks vascular endothelial growth factor (VEGF), has shown promising results and a survival benefit in patients with recurrent HGG ( Narayana et al, 2009 ; Huylebrouck et al, 2012 ; Morris, 2012 ). These findings led to the development of a pediatric trial within the PBTC-022 utilizing BVZ and CPT-11 in children with recurrent CNS tumors, including a HGG and diffuse intrinsic pontine glioma (DIPG) strata ( Gururangan et al, 2010 ).…”
Section: Treatment Strategies and Outcomesmentioning
confidence: 99%
“…Bevacizumab associated with temozolomide showed poor efficacy compared with temozolomide alone in patients with first recurrence of grades II–III glioma without 1p19q codeletion ( 18 ). Retrospective studies suggest that bevacizumab-based combination treatments or bevacizumab alone may be a strategy for alkylating agent-refractory grade III glioma, defined as progressive disease after temozolomide ( 19 22 ). Few prospective studies (phase II) showed a potential interest of bevacizumab as rescue treatment for recurrent grade III glioma ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%